Abundance and parasitism of clover root weevil (Sitona lepidus) and Argentine stem weevil (Listronotus bonariensis) in pastures - Gerard, P.J.; Vasse, M.; Wilson, D.J. (New Zealand Plant Protection, 2012)
The period from 2006 to 2010 in the North Island encompasses the widespread establishment of Irish Microctonus aethiopoides for the biocontrol of clover root weevil (Sitona lepidus) and a severe drought in 2008 that greatly reduced host availability This parasitoid occupies the same pasture habitat as Microctonus hyperodae a parasitoid with a similar life cycle introduced to control Argentine stem weevil (Listronotus bonariensis) A retrospective study was carried out on L bonariensis data and stored samples collected during S lepidus studies It was found that at all four initial M aethiopoides release sites L bonariensis populations were lowest in 2007 and 2008 while S lepidus populations were lowest in 2008 and 2009 Microctonus hyperodae parasitism levels were lowest in 2009 with overall regional means ranging from 5 in Manawatu to 11 in Waikato whereas corresponding Irish M aethiopoides parasitism levels were 43 and 72 respectively